FAKTOR-FAKTOR YANG MEMENGARUHI EARNING RESPONSES COEFFICIENT (STUDI EMPIRIS PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2013) - Fitriana Kania Dewi (Jurnal Akuntansi, 2015)
Badan Usaha Milik Negara abbreviated BUMN is a company that holds the key sectors of the major needs in Indonesia, to expand the company's business lines, then 20 BUMN began to sell shares in the Indonesia Stock Exchange and have to publish financial statementsÂ  which contains earnings information.The purpose of this study is to examine the influence of audit firm size, leverage, firm size and market to book ratio on earning response coefficient. The population of this research are all BUMN companies listed in the Indonesia stock exchange 2011-2013. The sampling technique in this research was purposive sampling. From 20 research sample, there are 15 companies qualified as a sample. Multiple regression analysis was employed to analyse data . The result that simultaneous all variable have positive effects on earning response coefficient, partially audit firm size, firm size and market to book ratio have positive effect on ERC.Â Keywords : Audit Firm Size, Leverage, Firm Size, Market To Book Ratio, Earning Responses Coefficient